Islamic philosophy, theology and mysticism : a short introduction - Fakhry, Majid (Oxford : Oneworld Publication, 2000)
'From the introduction of Greek philosophy into the Muslim world in the eighth century to modern times, this book charts the evolution and interaction of philosophy, theology and mysticism in the Islamic context.'--BOOK JACKET.
1. The Transmission of Ancient Philosophy and Science -- 2. Early Religious and Political Conflicts -- 3. The Dawn of Systematic Philosophy and Free Thought in the Ninth Century -- 4. Neoplatonism and Neopythagoreanism in the Tenth and Eleventh Centuries -- 5. Interactions of Philosophy and Dogma -- 6. Philosophy and Mysticism -- 7. The Resurgence of Peripatetic Philosophy in Al-Andalus -- 8. The Progress of Anti-Rationalism and the Onset of Decline -- 9. Illuminationism (Ishraq) and the Reconciliation of Neoplatonism and Sufism -- 10. Modern and Contemporary Trends -- App. 1. The Chief Philosophical Translations -- App. 2. Two Leading Mu'tazilite Scholars.
This publication reissued 2000
Bibliography: p. 148-153
Keywords: Philosophy, Islamic